2020
DOI: 10.1038/s41598-020-64509-z
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Hybrid Method to Automatically Diagnose Periodontal Bone Loss and Stage Periodontitis

Abstract: We developed an automatic method for staging periodontitis on dental panoramic radiographs using the deep learning hybrid method. A novel hybrid framework was proposed to automatically detect and classify the periodontal bone loss of each individual tooth. The framework is a hybrid of deep learning architecture for detection and conventional CAD processing for classification. Deep learning was used to detect the radiographic bone level (or the CEJ level) as a simple structure for the whole jaw on panoramic rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
101
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(129 citation statements)
references
References 35 publications
1
101
0
1
Order By: Relevance
“…RBL measurement is performed by evaluating the quantitative and qualitative perspectives of imaginable interproximal bone, which includes the distance between the cement-enamel junction (CEJ) and the most coronal level, where the periodontal ligament interval is considered to have a normal width [ 12 ]. Both RBL and %RBL classifications are related to the loss of bone tissue the teeth are connected, resulting in spontaneous loss of the teeth in the future [ 10 , 13 ]. All these classifications have emerged from an effort to find an accurate indicator of the oral and dental health status.…”
Section: Introductionmentioning
confidence: 99%
“…RBL measurement is performed by evaluating the quantitative and qualitative perspectives of imaginable interproximal bone, which includes the distance between the cement-enamel junction (CEJ) and the most coronal level, where the periodontal ligament interval is considered to have a normal width [ 12 ]. Both RBL and %RBL classifications are related to the loss of bone tissue the teeth are connected, resulting in spontaneous loss of the teeth in the future [ 10 , 13 ]. All these classifications have emerged from an effort to find an accurate indicator of the oral and dental health status.…”
Section: Introductionmentioning
confidence: 99%
“…CNNs have shown excellent results in the analysis of radiographic images when compared to the results by medical experts. Previous studies have shown that deep learning can be used to recognize anatomical structures, find anomalies, measure the distance, and classify structures in medical images 1,[3][4][5][6][7][8][9][10][11][12][13][14][15] . However, in most studies, object detection was conducted manually, and tasks were limited to performing simple measurements, comparisons, or classifications.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, CNNs have been extensively used in many fields. In the healthcare industry, numerous studies have reported that a CNN can be used to analyze and diagnose medical images [1][2][3][4][5][6][7] . CNNs have also been used to better interpret the complexities of medical imaging by revealing patterns in large numbers of data and acquiring essential information to gain more knowledge 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In dental radiology, AI has been used for a range of purposes. Detection of dental caries [ 14 , 15 , 16 , 17 ], apical lesions [ 18 ], periodontal bone loss [ 19 , 20 , 21 ], tooth fractures [ 22 ] or sinusitis [ 23 ] is already possible with the use of AI. The reported accuracies for most of these tasks are promising, and the first AI tools for dental diagnostics are currently entering the market.…”
Section: Introductionmentioning
confidence: 99%